Predictive Value of Hyperintense Acute Reperfusion Marker in Transient Ischemic Attacks: Stroke Recurrence and TOAST Classification - Sang-Hoon Han; Kyu-Sun Yum (Brain Sciences)
Background: Transient ischemic attack (TIA) is a recognized precursor of stroke that also indicates a high risk of recurrence. The Hyperintense Acute Reperfusion Marker (HARM), which is linked to blood–brain barrier disruption, may serve as a novel imaging biomarker for TIA. Methods: A retrospective cohort study of 715 patients with TIA evaluated the predictive value of HARM for stroke recurrence and its association with TOAST subtype. Imaging findings, including those of diffusion-weighted imaging, were analyzed using logistic regression. Results: HARM-positive patients had significantly higher recurrence rates at 3 months (20.9%; odds ratio [OR] = 5.3) and 1 year (30.2%; OR = 5.8) compared to HARM-negative patients, relative to other imaging markers (p < 0.001). HARM was significantly associated with the cardioembolic stroke (p < 0.001). Conclusions: HARM is a promising imaging biomarker for predicting stroke recurrence and etiology in patients experiencing TIA. Incorporating HARM into clinical frameworks may enhance diagnostic and prognostic accuracy.